artisipasi Penerima Bantuan Dalam Implementasi Program Rumah Swadaya di Kelurahan Gates Nan XX - Rivani, Eji; Alfitri; Nini Anggraini (LPPM STISIP IMAM BONJOL, 2025)
The Self-Help Housing Stimulant Assistance Program (BSPS) is a government program aimed at improving access to decent housing for low-income communities (MBR). This study examines the participation of community members receiving assistance in the BSPS implementation in Gates Nan XX Village, Lubuk Begalung Subdistrict, Padang City. Using a qualitative descriptive method, data was collected through in-depth interviews and document analysis with purposive sampling. Max Weber's Social Action Theory was applied to analyze the forms of participation. Findings reveal that community members actively engaged in planning, implementation, and utilization phases through organizing aid recipient groups, contributing self-help resources, and selecting workers. This participation fosters a sense of responsibility and ownership among residents.